A novel chrysin derivative produced by gamma irradiation attenuates 2, 4-dinitrochlorobenzene-induced atopic dermatitis-like skin lesions in Balb/c mice. (June 2019) - Song, Ha-Yeon; Kim, Woo Sik; Mushtaq, Sajid; Park, Ji Min; Choi, Sung-Hyun; Cho, Jae-Woo; Lim, Seung-Taik; Byun, Eui-Baek
Abstract: Gamma irradiation is a useful technology to change the physical and biological properties of natural molecules. In this study, we investigated whether gamma irradiation improve properties of chrysin as an anti-inflammatory candidates. Chrysin was converted into two compounds (CM1 and CM2) by gamma irradiation. We determined the therapeutic potential of these compounds in bone marrow-derived macrophages and 2, 4-dinitrochlorobenzene (DNCB)-induced atopic dermatitis (AD)-like skin lesions in Balb/c mice. The structural changes to chrysin led to the reduction of cytotoxicity without loss of anti-inflammatory properties in BMDMs. Purified CM2 inhibited lipopolysaccharide (LPS)-induced overexpression of nitric oxide, tumor necrosis factor-α, interleukin (IL)-6, and surface molecules without cytotoxicity in BMDMs, while CM1 revealed strong cytotoxicity. Furthermore, treatment with CM2 significantly alleviated AD-like skin symptoms and clinical signs in DNCB-induced AD mice model. The suppression of AD mediated by CM2 treatment was accompanied by decrease inflammatory T cell cytokines (IFN-γ, IL-5, IL-4, and IL-17). The chemical structure of CM2 and structural transformation mechanism were determined by nuclear magnetic resonance and mass spectrometry. Our study findings provide evidence that CM2 produced by gamma irradiation of chrysin can be an attractive therapeutic agent for AD. Highlights: Gamma irradiation produced a novel chrysin derivative by hydroxyethylation. A novel chrysin derivative exhibited anti-inflammatory activity in LPS-stimulated BMDMs without cytotoxicity. A novel chrysin derivative attenuated DNCB-induced AD-like symptoms in Balb/c mice. A novel chrysin derivative reduced DNCB-induced Th1-, Th2-, and Th17-type cytokines in Balb/c mice. A novel chrysin derivative might be a candidate for treatment of atopic dermatitis.